Modelling and computation in engineering : proceedings of the International Conference on Modelling and Computation in Engineering, CMCE 2010, Hong Kong, 6-7 November 2010 /: proceedings of the International Conference on Modelling and Computation in Engineering, CMCE 2010, Hong Kong, 6-7 November 2010. (©2011) - Unknown
No abstract available